The American Civil War and the wars of the Industrial Revolution - Reid, Brian Holden; Keegan, John, 1934-2012. (London : Cassell, 1999)
This book focuses on the strategic and operational dimensions of the campaigns of the Civil War, showing how such factors as generalship, organization, intelligence and logistics affected the decisions of the battlefield.
Introduction, war and industrialization -- 1. The Crimean War, 1854-6 -- 2. The American Civil War: the war takes shape, 1861-2 -- 3. The American Civil War: the year of trial and hope, 1862-3 -- The American Civil War: Confederate collapse, 1864-5 -- The German wars of unification, 1864, 1866, 1870-71 -- Afterword.
Series statement on jacket.
Includes bibliographical references (pages 218-219) and index.
Keywords: Geschichte 1864-1871.; 1800-1899; Military art and science -- History -- 19th century; Industrial revolution; Industrialization -- History -- 19th century